Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/md.0000000000027513
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bleeding symptoms among young adults in Saudi Arabia, a national survey

Abstract: Prevalence of bleeding disorders vary due to several factors including geographical location. Mild bleeding disorders can lead to iron deficiency, morbidity, and in severe cases mortality. Quantification of haemorrhagic symptoms is a key component in management of bleeding disorders and a challenging task for clinicians.An abridged version of MCMDM-1vWD questionnaire with validated Arabic translation was used to quantify bleeding disorders in adult students (n = 1138) in 4 different regions of Kingdom of Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…In this study, the prevalence of self-reported epistaxis was 43.4%, which was lower than that reported in another study (71%) [ 13 ]. Additionally, the prevalence of epistaxis in this study was significantly higher in females than in males, in contrast to the findings of another study conducted in Saudi Arabia [ 14 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the prevalence of self-reported epistaxis was 43.4%, which was lower than that reported in another study (71%) [ 13 ]. Additionally, the prevalence of epistaxis in this study was significantly higher in females than in males, in contrast to the findings of another study conducted in Saudi Arabia [ 14 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This study also conducted a regression analysis to correlate bleeding after surgery to other bleeding symptoms. A negative correlation against menorrhagia was observed whereas no other significant correlation was reported for the other symptoms [ 3 ].…”
Section: National Surveysmentioning
confidence: 99%
“…Multiple researchers in Saudi Arabia have highlighted the cause and the frequency of such medical conditions [ 1 , 2 ]. Their published literature concluded that platelet disorders, von Willebrand disease (vWD), and hemophilia are some of the most prevalent bleeding disorders in the kingdom [ 3 ]. As the genetic factor is one of the major causes of bleeding disorders, consanguinity magnifies the prevalence of hereditary bleeding disorders among the Saudi population [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, the prevalence of epistaxis in the pediatric population is not well-documented. However, one study showed a prevalence of around 27% among young adults [ 3 ]. Recurrent epistaxis lacks a consensus definition regarding the duration or frequency of episodes, although some studies consider it as five or more episodes per year [ 4 ].…”
Section: Introductionmentioning
confidence: 99%